Physical activity RX: development and implementation of physical activity counselling and prescription learning objectives for Canadian medical school curriculum - Capozzi, Lauren C; Lun, Victor; Shellington, Erin M; Nagpal, Taniya S; Tomasone, Jennifer R; Gaul, Catherine; Roberts, Arielle; Fowles, Jonathon R (Canadian Medical Education Journal, 2022)
Physical activity is an important component of health and well-being, and is effective in the prevention, management, and treatment of numerous non-communicable chronic diseases. Despite the known health benefits of physical activity in all populations, most Canadians do not meet physical activity recommendations. Physicians play a key role in assessing, counselling, and prescribing physical activity. Unfortunately, many barriers, including the lack of adequate education and training, prevent physicians from promoting this essential health behaviour. To support Canadian medical schools in physical activity curriculum development, a team of researchers, physicians, and exercise physiologists collaborated to develop a key set of learning objectives deemed essential to physican education in physical activity counselling and prescription. This commentary will review the newly developed Canadian Physical Activity Counselling Learning Objectives and give case examples of three Canadian medical schools that have implemented these learning objectives.